Uji hedonik abon sukun (Artocarpus altilis) dengan campuran kerang ale-ale (Metetrix sp) - Jumiar, Alfath Desita; Rifkowaty, Encik Eko; Sahid, Abdul (AGRICOLA, 2024)
Shredded is a type of processed dry food product with a distinctive shape made from meat that is boiled, cut, seasoned, fried and then pressed. This study aims to find out the level of preference of panelists for ale-ale breadfruit shredded products based on color, aroma, taste and texture parameters. This study is an experimental research by making shredded breadfruit mixed with ale-ale with 100% breadfruit treatment as a control, 75% breadfruit mixed with 25% ale-ale as treatment I, breadfruit 50% mixed with 50% ale-ale as treatment II. The acceptance rate of panelists for ale-ale breadfruit shredded products used a hedonic test with taste, aroma, color and texture parameters, with a measurement scale from 1 to 9. The panelists were 30 people who were not trained. Data analysis uses analysis of variance (ANOVA) and continues with the Duncan test if there are differences. Based on the research, shredded fish with 75% breadfruit treatment and 25% ale-ale obtained a better acceptance value, namely 6 based on taste parameters, and texture with an acceptance value of 7.03. Shredded fish with 100% breadfruit treatment obtained a better acceptance score of 6.8 based on color parameters. Meanwhile, the aroma parameters of the third shredded treatment obtained a neutral acceptance value.